Correlation Analysis Between Serum Uric Acid, Prealbumin Level, Lactate Dehydrogenase, and Severity of COVID-19 - Jin, Zhenmu; Zheng, Mo; Shi, Jichan; Ye, Xinchun; Cheng, Fang; Chen, Que-Lu; Huang, Jianping; Jiang, Xian-Gao (Frontiers in Molecular Biosciences, 2021)
Objective: to analyze the correlation between serum uric acid, prealbumin level, lactate dehydrogenase (LDH) and the severity of COVID-19. Methods: The data of 135 patients with COVID-19 were collected and they were divided into non severe group (110 cases) and severe group (25 cases) according to the severity of illness. 60 cases with normal physical examination in the same period and 17 cases diagnosed with other viral pneumonia in the past 5 years were selected as the control group to analyze the correlation between detection index and the severity of COVID-19. Results: the levels of albumin, prealbumin, serum uric acid and LDH in severe group were significantly different from those in healthy control group (P < 0.01); the level of prealbumin, serum uric acid, LDH and CRP in severe group were significantly different from those in other viral pneumonia group (P < 0.01). Serum albumin and prealbumin were positively correlated with oxygenation index (P < 0.001), while LDH was negatively correlated with oxygenation index (P < 0.001). Conclusion: serum albumin, prealbumin, oxygenation index and LDH are risk factors of COVID-19.